Analysis of The Effect of Service Quality on Public Satisfaction with Motor Vehicle Testing Services at The Bukittinggi City Transportation Department - Asnil Asnil; Sabri Sabri; Kuliman Kuliman; Anne Putri (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
This study investigates the effect of service quality on community satisfaction in motor vehicle testing services at the Department of Transportation of Bukittinggi City. Despite the increasing demand for public services, empirical evidence on how multidimensional service quality influences user satisfaction in the context of mandatory vehicle testing remains limited, particularly in local government settings. This research addresses this gap by employing a quantitative explanatory design, conceptualizing service quality through five dimensions: tangible, reliability, responsiveness, assurance, and empathy. Data were collected from 100 service users using a structured and validated questionnaire and analyzed through multiple linear regression. The findings reveal that all dimensions of service quality have a positive and statistically significant effect on community satisfaction, both partially and simultaneously. The model explains 76.8% of the variance in community satisfaction (R² = 0.768), indicating strong explanatory power. Among the dimensions, responsiveness emerges as the most influential factor, highlighting the critical role of prompt and adaptive service delivery in shaping user perceptions. This study contributes to the public service literature by providing empirical evidence on the relative importance of service quality dimensions in a regulatory service context. Practically, the findings suggest that improving responsiveness and reliability should be prioritized to enhance service effectiveness and sustain public trust.